Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Dinas Pemadam Kebakaran dan Penyelamatan Kota Surabaya - Harini Widayanti; Muhammad Rizky Ramadhan (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims analyze the influence of work motivation on employee performance at the Fire and Rescue Department of Surabaya City. The theory applied is Maslow's hierarchy of needs, which categorizes motivation into five levels: physiological needs, safety needs, social needs, esteem needs, and self-actualization. This research employs a quantitative approach using a survey method by distributing questionnaires to employees as respondents. The collected data were analyzed using simple linear regression. The results indicate that work motivation has a significant effect on employee performance. The two indicators with the greatest influence are physiological needs and self-actualization. These findings suggest that fulfilling basic needs and providing opportunities for self-development are crucial in enhancing the performance of the personnel.